A Scientist’s Guide for Engaging in Policy in the United States - Hetherington, Elizabeth D.; Phillips, Alexandra A. (Frontiers in Marine Science, 2020)
It is critical that research and scientific expertise inform legislative decisions and guide effective policy. However, significant communication gaps persist between science and policy communities. While interest in science policy among researchers has substantially increased in recent decades, traditional academic and research careers rarely provide formal training or exposure to the inner workings of government, public policy, or communicating scientific findings to broad audiences. Here, we offer ten practical steps for scientists who want to participate in science policy, with a focus on state and federal policy in the United States. We first include a primer to government structure and tailoring science communication for a policymaker audience. We then provide action-oriented steps that focus on arranging and successfully navigating meetings with government officials. Finally, we suggest structural steps in academia that would provide resources and support for students, researchers, and faculty who are interested in policy. We offer our perspective, as early-career marine scientists who have participated in policy discussions at state and federal levels and are current participants in the American Geophysical Union’s “Voices for Science” program. We offer potential pathways for engagement in science policy, with a goal of providing researchers with actions to effectively reach stakeholders and integrate policy into their research. Lastly, we hope to activate further conversations on best practices for science policy engagement, particularly for researchers interested in careers at the science policy interface.